Breaking the Stereotype of the Damsel in Distress: Exploring Gender and Social Class Dynamics in Netflix’s Damsel - Putri, Dahlia Salsabila Ryana (Serat: Journal of Literary & Cultural Studies, 2024)
The “damsel in distress” trope in literature and media has been prevalent for centuries, stereotyping young female characters as in need of rescue by male protagonists, who are often depicted as coming from a higher social class. This archetype has become deeply ingrained in societal consciousness, shaping perceptions of gender roles and social hierarchies over the course of history. Adopting critical analysis and taking feminist outlooks on gender and social class dynamics, this study examines the portrayal of Elodie, a character that deviates from the classic “damsel in distress” archetype, in the recently released Netflix film Damsel (2024). The purpose of this study is to analyze how Elodie is depicted in Damsel and to explore the way the film challenges conventional gender and social class norms in order to prove that the film breaks the damsel stereotype. Through the findings and analyses, it is apparent that Elodie’s character breaks away from traditional gender and social class expectations, presenting a more empowered depiction of female characters.